Effect of Cross Wind on Performances of Natural Draft Counterflow Cooling Tower Outlet. Issue 11 (13th August 2017) - Zhao, Shun-An; Wang, Ming-Ren; Li, Lu-Jun; Du, Cheng-Qi
ABSTRACT: The cooling efficiency of the counterflow natural draft cooling tower could be reduced by a cross wind. Therefore, it is necessary to study the cross-wind impact for optimizing the design. In this paper, a three-dimensional numerical model is used to study the influence of the cross wind on the pressure loss coefficient at the outlet of the counterflow natural draft cooling tower. The results show that an obvious additional draft is formed when the cross-wind velocity is more than four times of the mean velocity at the fill section. A formula to quantitatively analyze the influence of the cross wind is given in this paper.